2020
DOI: 10.3390/ijerph17030777
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Concentrations of Ultrafine Particles in the Plumes of Ships in the Vicinity of Major Harbors

Abstract: Marine traffic in harbors can be responsible for significant atmospheric concentrations of ultrafine particles (UFPs), which have widely recognized negative effects on human health. It is therefore essential to model and measure the time evolution of the number size distributions and chemical composition of UFPs in ship exhaust to assess the resulting exposure in the vicinity of shipping routes. In this study, a sequential modelling chain was developed and applied, in combination with the data measured and col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 90 publications
0
24
0
Order By: Relevance
“…The FSC limits and emissions control areas are described in more detail in IMO MARPOL Annex VI, Regulation 14 (IMO, 2020b). The decline in the real FSC of marine vessels has been shown to follow the FSC restrictions well (Kattner et al, 2015;Pirjola et al, 2014); therefore, the FSC limits can be expected to resemble the real maximum FSC of the fuels used. However, Pirjola et al (2014) reported that during the FSC restriction period of 1.50 m/m% (before July 2010), some vessels were already using fuels with an FSC of less than 1.00 m/m%.…”
Section: Introductionmentioning
confidence: 98%
“…The FSC limits and emissions control areas are described in more detail in IMO MARPOL Annex VI, Regulation 14 (IMO, 2020b). The decline in the real FSC of marine vessels has been shown to follow the FSC restrictions well (Kattner et al, 2015;Pirjola et al, 2014); therefore, the FSC limits can be expected to resemble the real maximum FSC of the fuels used. However, Pirjola et al (2014) reported that during the FSC restriction period of 1.50 m/m% (before July 2010), some vessels were already using fuels with an FSC of less than 1.00 m/m%.…”
Section: Introductionmentioning
confidence: 98%
“…As for road traffic, the influence of ship emissions on air quality induces pollution gradients in the city. Karl et al (2020) thus found out that, in residential areas up to 3600m from a major harbour, the ultrafine particle concentrations were increased by a factor of two or more compared with the urban background.…”
Section: Innovative Combinations Of Modelsmentioning
confidence: 90%
“…Murena et al (2018) also treated the ships in maneuvering and navigation modes as fixed point emission sources. In another group of studies, a line emission source model was widely applied to simulate the moving ships in maneuvering or cruising mode (Poplawski et al, 2011;Kotrikla et al, 2013;Deniz and Kilic, 2010;Lucialli et al, 2011). In the line source (LS) model setup, the ship emission is assumed to be constantly emitted along the entire ship route, which is assumed to be a straight line.…”
Section: Introductionmentioning
confidence: 99%
“…In the line source (LS) model setup, the ship emission is assumed to be constantly emitted along the entire ship route, which is assumed to be a straight line. In some other cases, ships in hoteling or maneuvering modes were treated as area sources (Kotrikla et al, 2013;Formentin, 2017;Abrutytė et al, 2014); however, this assumption is not commonly used to treat ship emissions.…”
Section: Introductionmentioning
confidence: 99%